Answer: tan²A – sin²A = tan² A sin²A from LHS, tan²A -sin²A = (sin²A / cos²A) – sin²A……[tan A=sin A/cos A] = (sin²A – sin²Acos²A) / cos²A = sin²A (1- cos²A) / cos² A [tan A = sinA / cos A] = tan²A sin²A= RHS .•. hence proved Step-by-step explanation: Hope it is helpful… Log in to Reply

Answer:tan²A – sin²A = tan² A sin²A

from LHS,

tan²A -sin²A

= (sin²A / cos²A) – sin²A……[tan A=sin A/cos A]

= (sin²A – sin²Acos²A) / cos²A

= sin²A (1- cos²A) / cos² A [tan A = sinA / cos A]

= tan²A sin²A= RHS

.•. hence proved

Step-by-step explanation:Hope it is helpful…